GENDER INEQUALITY AND THE SCOURGE OF HIV/AIDS: The Bahai Religio-Philosophical Solution - Akhilomen, Don (Journal of Dharma, 2011)
One of the most complex challenges facing contemporary Africa is how to resolve the frightening health crises, especially that posed by the HIV/AIDS pandemic. With the continent hosting about 70% of the world's total population of infected people, HIV/AIDS is correctly to be described as African holocaust. I The very high incidence of HIV/AIDS in Africa, and the even more worrying overwhelming preponderance of female infection, rightly provokes the thinking that there is a gender dimension to the HIV/AIDS scourge in the sub-Saharan continent of Africa.